PANCASILA AS THE BASIS AND IDEOLOGY OF THE STATE: IMPLEMENTATION IN NATIONAL AND STATE LIFE - Harianja, Ardiansyah Putra; Sinaga, Rudi Salam (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The purpose of this article is to examine the strategic role of Pancasila as the foundation of the state and national ideology of Indonesia in shaping national character and identifying the challenges of its implementation amid the currents of globalization and digitalization. As an open ideology, Pancasila embodies universal values such as religiosity, humanity, unity, democracy, and social justice, which serve as guiding principles in national and civic life. This study uses a descriptive qualitative approach with a literature review method, where data were collected through analysis of academic literature, policy documents, and previous research findings. The data analysis technique used is content analysis to explore the contextual dynamics of Pancasila values within Indonesian society. The findings show that although Pancasila is embedded in various educational, legal, and social policies, its implementation still faces serious challenges, such as the influence of global individualistic culture, the penetration of digital technology that fosters misinformation and polarization, and socioeconomic inequalities that weaken the spirit of justice. Therefore, a progressive and participatory revitalization strategy is needed, including strengthening character education, renewing practical curricula, and promoting national values in digital spaces. In conclusion, Pancasila remains relevant as the moral and ideological foundation of Indonesia, provided it continues to be contextualized in response to contemporary challenges and supported by the collective commitment of all elements of the nation.